Usefulness of a Nocturnal SOREMP for Diagnosing Narcolepsy with Cataplexy in a Pediatric Population. Issue 6 (1st June 2015) - Reiter, Joel; Katz, Eliot; Scammell, Thomas E.; Maski, Kiran
Abstract: Study Objectives: We investigated the diagnostic accuracy of a nocturnal sleep onset rapid eye movement sleep period (nSOREMP) for the identification of narcolepsy with cataplexy (N+C) among children and adolescents referred to the sleep laboratory for an overnight polysomnography (PSG) and multiple sleep latency test (MSLT). Design: Retrospective chart review of sleep clinic notes and PSG and MSLT reports. Setting: Boston Children's Hospital sleep laboratory and outpatient clinics. Patients: All patients 6–18 y old, referred for consecutive PSG and MSLT for the evaluation of central hypersomnias, between January 2005 and January 2014. Measurements and Results: We analyzed the records of 148 patients and established diagnostic categories using the International Classification of Sleep Disorders, 2 nd Edition. Patient diagnoses included narcolepsy with cataplexy (28.4%), narcolepsy without cataplexy (8.1%), other hypersomnia conditions (9.5%), delayed sleep phase syndrome (12.2%), behaviorally induced insufficient sleep syndrome (4.1%), other sleep disorders (obstructive sleep apnea, periodic limb movements of sleep; 6.8%), isolated cataplexy (2%), and various diagnoses (29.1%). There were 54.8% of the N+C patients who had an nSOREMP, but only 2.4% of all other patients had an nSOREMP. The specificity of an nSOREMP for detection of N+C was high at 97.3% (95% confidence interval [CI]: 92.2–99.4%), but the sensitivity was moderate at 54.8% (95% CI: 38.7–70.2%). Overall, the positive predictive value of an nSOREMP for the diagnosis of N+C was 88.5% (95% CI: 69.8–97.4%). Conclusions: In children, the presence of an nocturnal sleep onset rapid eye movement sleep period is highly suggestive of narcolepsy with cataplexy and provides further evidence of rapid eye movement sleep dysregulation in this condition.